NEGATIVE PRESSURES OF DETERGENTS IN THE METAL BERTHELOT TUBE - Hiro, Kazuki; Fukuoka, Hiroshi; Nakamura, Shigeto; Wada, Tadahiro; Fujiwara, Junsuke (MATTER: International Journal of Science and Technology, 2019)
Liquids can withstand negative pressures unless cavitation occurs. When any objects covered with dirt are in liquids under negative pressures, the objects are stretched by the surrounding liquids. Therefore, the dirt may be removed from the objects. Thus, a final goal of this study is to investigate cleaning effects of negative pressures, and, in this paper, as the first step to the goal, negative pressures of some kinds of commercial liquid detergents are measured by the Berthelot method using a metal tube. The method generates static negative pressures, which increases with a repetition of a cycle through a quasi-isochoric process of a system composed of a metal tube, a sample liquid, and a sealing plug. Negative pressures for a domestic detergent recommended for removal of oils on metal surfaces, attained to ca. -20 MPa, the highest of the method, within only ca. 230 cycles. Furthermore, the pressure was attained without any de-gassing treatments to the tube recommended for high negative pressures. On a basis of composition of the detergent, industrial detergents were tested. Detergents including non-ionic surfactants generated similar high negative pressures, while that of an anion surfactant never attained.